Pemberdayaan Masyarakat Dalam Pengurangan Resiko Bencana Banjir Pada Kelurahan Tunggul Hitam Kota Padang - Handrina, Emi (CV. ITTC INDONESIA, 2024)
In increasing the role of the community in disaster management, the Padang City government facilitated the formation of a Disaster Preparedness Group (KSB) in Dadok nggul Hitam sub-district. Dadok nggul Hitam sub-district is one of the flood-prone areas in Padang City. The aim of this research is to explain and describe community empowerment in reducing the risk of flood disasters in Dadok nggul Hitam Padang Village. Based on the results of the research, conclusions can be drawn about community empowerment carried out by the Padang City BPBD and the KSB of Dadok nggul Hitam Padang Village.;. However, the empowerment carried out has not been optimal due to the high level of community dependency and the unclear duties of the KSB of Dadok nggul Hitam Padang Subdistrict in carrying out community empowerment. The suggestion is that it is hoped that the government can be more serious in empowering the community, especially regarding the frequent flood disasters, there will be increased more effective training carried out by BPBD Padang City and KSB Dadok nggul Hitam Subdistrict for the community by forming SOPs and The main tasks and functions are clearer and more focused on the KSB members of Dadok nggul Hitam Subdistrict and it is hoped that the government will prioritize flood disasters the same as the priority given to earthquake and tsunami disasters, because every disaster will cause loss of life and property for the community.